2002
DOI: 10.1161/hc0802.104407
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Coronary Artery Disease With Recombinant Fibroblast Growth Factor-2

Abstract: Background-Single-bolus intracoronary administration of fibroblast growth factor-2 (FGF2) improved symptoms and myocardial function in a phase I, open-label trial in patients with coronary artery disease. We conducted the FGF Initiating RevaScularization Trial (FIRST) to evaluate further the efficacy and safety of recombinant FGF2 (rFGF2). Methods and Results-FIRST is a multicenter, randomized, double-blind, placebo-controlled trial of a single intracoronary infusion of rFGF2 at 0, 0.3, 3, or 30 g/kg (nϭ337 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
382
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(392 citation statements)
references
References 35 publications
6
382
0
4
Order By: Relevance
“…Given that stress-induced relapse is a significant problem in the treatment of anxiety disorders, the finding that FGF2 reduces reinstatement has potentially important clinical implications. Although FGF2 has been trialed in humans as a potential inducer of angiogenesis (Laham et al, 2000;Lederman et al, 2002;Simons et al, 2002), until now it has not been considered as a potential pharmacological adjunct to exposure therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that stress-induced relapse is a significant problem in the treatment of anxiety disorders, the finding that FGF2 reduces reinstatement has potentially important clinical implications. Although FGF2 has been trialed in humans as a potential inducer of angiogenesis (Laham et al, 2000;Lederman et al, 2002;Simons et al, 2002), until now it has not been considered as a potential pharmacological adjunct to exposure therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, single-bolus intracoronary FGF2 infusion showed transient beneficial effects, including reduction of angina symptoms, increase of treadmill tolerance and quality of life [237]. Transient beneficial effects were observed also in the phase II trial FIRST in which FGF2 was administered via intracoronary infusion [238]. In PAD patients, a positive response was observed in a phase I trial in which patients with symptoms of claudications and advanced peripheral arterial disease where given intra-arterial FGF2 infusion [239].…”
Section: Fgfs and Therapeutic Angiogenesismentioning
confidence: 96%
“…Thus, there has been great interest in novel therapeutic options, such as gene (reviewed in [2]) and stem cell therapy (reviewed in [3]), or even direct administration of proangiogenic cytokines [4]. In the case of growth factor-based therapy, although preclinical studies and initial clinical trials had suggested beneficial effects [5,6], doubleblinded clinical trials with large cohorts of patients failed to validate the efficacy [7][8][9]. These negative findings may have resulted from issues related to growth factor selection, monotherapy instead of combinatorial therapy, and/or timing of growth factor delivery.…”
Section: Introductionmentioning
confidence: 99%